2020
DOI: 10.3390/cancers12092467
|View full text |Cite
|
Sign up to set email alerts
|

Second-Generation Antiandrogen Therapy Radiosensitizes Prostate Cancer Regardless of Castration State through Inhibition of DNA Double Strand Break Repair

Abstract: (1) Background: The combination of the first-generation antiandrogens and radiotherapy (RT) has been studied extensively in the clinical setting of prostate cancer (PCa). Here, we evaluated the potential radiosensitizing effect of the second-generation antiandrogens abiraterone acetate, apalutamide and enzalutamide. (2) Methods: Cell proliferation and agarose-colony forming assay were used to measure the effect on survival. Double strand break repair efficiency was monitored using immunofluorescence staining o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 41 publications
1
11
0
Order By: Relevance
“…Importantly, we have also shown, that downregulation of these key DNA repair genes was conserved when AR suppression through Abiraterone or Enzalutamide is combined with 2Gy radiation (a standard clinical fractionated dose). Thus, supporting the suggestion ( 25 ) that it is this key downregulation of key DSB DNA repair pathways that is responsible for our observed radiosensitizing effects with radiation. Our comparisons between one-hour pre-treatment and 24-hour pre-treatment have also shown that for maximal impact, complete AR suppression should be achieved before radiation over concurrent treatment, as even one-hour post-radiation, where DNA damage should be at its maximum, we observed decreased levels of both key NHEJ and HR proteins.…”
Section: Discussionsupporting
confidence: 92%
“…Importantly, we have also shown, that downregulation of these key DNA repair genes was conserved when AR suppression through Abiraterone or Enzalutamide is combined with 2Gy radiation (a standard clinical fractionated dose). Thus, supporting the suggestion ( 25 ) that it is this key downregulation of key DSB DNA repair pathways that is responsible for our observed radiosensitizing effects with radiation. Our comparisons between one-hour pre-treatment and 24-hour pre-treatment have also shown that for maximal impact, complete AR suppression should be achieved before radiation over concurrent treatment, as even one-hour post-radiation, where DNA damage should be at its maximum, we observed decreased levels of both key NHEJ and HR proteins.…”
Section: Discussionsupporting
confidence: 92%
“…In general, since the potential for the novel antiandrogens as standalone therapeutic had reached a plateau for use in advanced PCa, it is far more likely that the next wave of therapeutic investigation will be focused on the combination of this class of antiandrogen therapy with other treatments such as RT and chemotherapy. In fact, as reported by Elsesy et al (52), the use of second-generation antiandrogens radiosensitizes PCa via the inhibition of the DNA double-strand break repair machinery. These results are in accordance with recent preclinical studies (53) reporting that enzalutamide has a radiosentization role, increasing the effect of ionizing radiation.…”
Section: Second-generation Adtmentioning
confidence: 77%
“…In fact, as reported by Elsesy et al. ( 52 ), the use of second-generation antiandrogens radiosensitizes PCa via the inhibition of the DNA double-strand break repair machinery. These results are in accordance with recent preclinical studies ( 53 ) reporting that enzalutamide has a radiosentization role, increasing the effect of ionizing radiation.…”
Section: New Scenariosmentioning
confidence: 77%
“…These results indicate a potential for combining the use of radiolabeled PSMA agents with available radiosensitizing agents. One example of emerging agents with proposed radiosensitizing properties are the second-generation anti-androgens, such as Enzalutamide, already in clinical use for metastatic castration resistant prostate cancer [ 36 , 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%